Mass media and the shaping of American feminism, 1963-1975 - Bradley, Patricia, 1941- (University Press of Mississippi, 2003)
Beginning in 1963 with the publication of Betty Friedan's The Feminine Mystique and reaching a high pitch ten years later with the televised mega-event of the "Battle of the Sexes"--The tennis match between Billie Jean King and Bobby Riggs-the mass media were intimately involved with both the distribution and the understanding of the feminist message. This mass media promotion of the feminist profile, however, proved to be a double-edged sword, according to Patricia Bradley, author of Mass Media and the Shaping of American Feminism, 1963-1975. Although millions of women learned about